A biochar-based amendment improved cadmium (Cd) immobilization, reduced its bioaccumulation, and increased rice yield - Han, Junnan; Wu, Donghai; Yang, John; Shi, Yuan; Abid, Ghassen; Wang, Lingjun; Li, Zhengguo (Frontiers in Environmental Science, 2024)
Cadmium (Cd) contamination in soil is of severe health and environmental concern because of its threatens to human health, food securitysafety, and ecosystem sustainability.The iIn situ stabilization of Cd has been recognized as a potentially economical technologytechnique for the remediationrehabilitation of Cd contaminated soil polluted with Cd. Recently, Bbiochar (BC) and activated carbon (AC) has recently received widespreadmuch attention as an eco-friendly and recyclable soil amendment, that which is more beneficial for plant growth, soil health, and remediationrestoration of contaminated soil. An experiment was performed in paddythe field to investigatestudy the effectsefficiency of twothree different types of BCbiochar: (maize straw biochar restoration in contaminated soils (Wu et al., 2019). Therefore, it is urgently needed to explore a sustainable and environmentally friendly soil amendment tothat can effectively reduce the Cd bioavailability in agricultural soils, and improve soil the condition of soil, and increaseproductivity of crops yield.Recently, biochar has been increasingly being applied toused for the mitigateion of heavy metal pollution in agricultural fields (Břendová et al., 2016;Chen et al., 2021). Biochar is generally produced bycharacterized as a highly carbonaceous, alkaline compound derived from the pyrolysis of biomass (Agricultural waste, wood, herbs, fruit shells, etc.)at high temperatures under oxygen-restricted or non-oxygenated environments at temperature between 400 °C and 700 °C (Blanco-Canqui, 2017)., Biocharwhich has a relatively high speculative surface and a wide pore size distribution, with the surface containing a considerable number ofconsiderable porosity, negatively chargedloaded superficial chemical functional groups (-OH, -COOH, C=O, S 2-, CO3 2-, PO4 3-, etc.), which can enhance theand strong absorption, complexation, and precipitation of Cd capacity that can enhance immobilize heavy metals in soil